Evaluation des options de performance managériale des dibiteries de Dakar et sa banlieue (Sénégal) - Orou Seko, M. (Université Cheikh Anta Diop de Dakar, 2015)
ABSTRACT IN ENGLISH: This study aims at evaluate managerial performance options of dibiteries in Dakar and its suburbs. To carry out, a cross-sectional study based on a questionnaire was conducted in 163 tenants of dibiteries. Data collected allowed us to estimate the efficiencies scores according DEA (Data Envelopement Analysis method). The pure technical efficiency scores were then used as a dependent variable in a Tobit model to identify the socioeconomic determinants of dibiteries’ efficiency. The mean scores of dibiteries efficiency show that they are globally inefficient. This inefficiency is more due to technical inefficiency than scale inefficiency. However most of these dibiteries (77.62%) evolve in a situation of scale economy with 7.89% of Hausa dibiteries, 33.55% Moorish dibiteries and 36.18 % of Senegalese dibiteries. The performance according to different types of dibiteries indicates that, on average, Hausa dibiteries are more efficient in terms of total and technical efficiency than Moorish and Senegalese dibiteries. Moreover, in terms of efficiency of scale, Senegalese dibiteries are more efficient than the other two. However, no statistical significant difference between the means was noted. Finally, the observed overall inefficiency of Hausa, Moorish and Senegalese dibiteries is more linked to their inappropriate size than poor management of their resources. Among the socioeconomic variables that may influence the efficiency of dibiteries, the nature of enterprise, the education level, the ownership title, the experience, the status of dibiterie operator have a significant impact on that efficiency. Actions on these determinants will further improve performance of dibiteries. ABSTRACT IN FRENCH: La présente étude a pour objectif d’évaluer les options de performance managériale des dibiteries de Dakar et sa banlieue. Pour ce faire, une étude transversale sur la base d’un questionnaire a été réalisée auprès de 163 dibitiers. Les données collectées nous ont permis d’estimer les scores d’efficience à partir de la méthode d’analyse par enveloppement des données (DEA). Les scores d’efficience technique pure ont ensuite été utilisés comme variables dépendantes dans un modèle Tobit pour identifier les déterminants socioéconomiques de l’efficience des dibiteries. Les scores moyens d’efficience des dibiteries montrent qu’elles sont inefficientes globalement. Cette inefficience est plus due à de l’inefficience technique qu’à de l’inefficience d’échelle. Cependant, la majorité de ces dibiteries (77,62%) évoluent dans une situation d’économie d’échelle avec 7,89% de dibiteries haoussas, 33,55% des dibiteries maures et 36,18% des dibiteries sénégalaises. La performance selon les différents types de dibiteries indique qu’en moyenne les dibiteries haoussas sont plus efficientes en termes d’efficience totale et technique que les dibiteries maures et sénégalaises. Par ailleurs, en termes d’efficience d’échelle, les dibiteries sénégalaises sont plus efficientes que les deux autres. Mais aucune différence statistiquement significative entre les moyennes n’a été notée. Enfin, l’inefficience globale observée des dibiteries haoussas, maures et sénégalaises est plus liée à leur taille inappropriée qu’à une mauvaise gestion de leurs ressources. Parmi les variables socioéconomiques pouvant influencer l’efficience des dibiteries, la nature de l’entreprise, le niveau d’instruction, le titre de propriété, l’expérience, le statut du “dibitier” ont eu un impact significatif sur cette efficience. Des actions sur ces déterminants permettront d’améliorer davantage la performance des dibiteries.